AQP5 Is a Novel Prognostic Biomarker in Pancreatic Adenocarcinoma - Chen, Guo; Song, Haiyang; Yang, Zelong; Du, Tianshu; Zheng, Yu; Lu, Zifan; Zhang, Kunpeng; Wei, Di (Frontiers in Oncology, 2022)
ABSTRACT Background: Pancreatic adenocarcinoma (PAAD) is a highly malignant tumor with a poor prognosis. The identification of effective molecular markers is of great significance for diagnosis and treatment. Aquaporins (AQPs) are a family of water channel proteins that exhibit several properties and play regulatory roles in human carcinogenesis. However, the association between Aquaporin-5 (AQP5) expression and prognosis and tumor-infiltrating lymphocytes in PAAD has not been reported. Methods: AQP5 mRNA expression, methylation, and protein expression data in PAAD were analysed using GEPIA, UALCAN, HAP, METHSURV, and UCSC databases. AQP5 expression in PAAD patients and cell lines from our cohort was examined using immunohistochemistry and western blotting. The LinkedOmics database was used to study signalling pathways related to AQP5 expression. TIMER and TISIDB were used to analyse correlations among AQP5, tumor-infiltrating immune cells, and immunomodulators. Survival was analysed using TCGA and Kaplan-Meier Plotter databases. Results: In this study, we investigated AQP5 expression in PAAD and determined whether the expression of AQP5 is a strong prognostic biomarker for PAAD. We searched and analysed public cancer databases (GEO, TCGA, HAP, UALCAN, GEPIA, etc.) to conclude that AQP5 expression levels were upregulated in PAAD. Kaplan-Meier curve analysis showed that high AQP5 expression positively correlated with poor prognosis. Using TIMER and TISIDB, we found that the expression of AQP5 was associated with different tumor-infiltrating immune cells, especially macrophages. We found that hypomethylation of the AQP5 promoter region was responsible for its high expression in PAAD. Conclusions: AQP5 can serve as a novel biomarker to predict prognosis and immune infiltration in PAAD.